The Pastoral Care of People with Visual Impairment in Poland. Contemporary Problems and Challenges - Dariusz Lipiec (Polonia Sacra)
The social and cultural as well as religious ongoing transformations in the Polish society influence the activity of the extraordinary pastoral care of people with visual impairment. The transformations cause various problems and challenges which the pastoral care has to face. Integration processes result in the fact that at the diocesan level more and more of the blind or visually impaired people satisfy their religious needs within the parish pastoral care and fewer of them use the special pastoral care which is addressed for them specifically. What is more, the secularization of the society results in the decrease of the number of people with disabilities who maintain their religious practice. It particularly concerns young people. The employment of priests who would be able to work for the pastoral care of people with visual impairment is a real challenge. The employment rate in this pastoral care is relatively low. Furthermore, the organization and coordination of the nationwide events becomes more and more challenging. The current problems and challenges in the centres for the blind children, teens and adults mainly result from the constantly changing state legislation. They mainly concern the possibility of engaging priests into the lives of their residents.